PELATIHAN PENGGUNAAN KOMIK MATEMATIKA PADA SISWA SMP - ferdiani, rosita dwi; Fayeldi, Trija; Murniasih, Tatik Retno (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2019)
abstract: Mathematics is a subject that is still considered difficult by some students. This is because, mathematics is always associated with calculations, formulas, and graphics. In addition there is material in mathematics that is abstract. So students must imagine something abstract in order to understand the material. For this reason, students need intermediaries who make it easy to understand something abstract. This intermediary is called learning media. Based on interviews with mathematics teachers at MTs Miftahul Ulum Ngembal and PGRI Tutur Islamic Middle School, the procurement of mathematics learning media is still lacking. The learning media used are worksheets. The appearance of worksheets is not very interesting and only contains a summary of material and questions, making students less motivated to learn worksheets. They study when the test will be held. This causes learning outcomes, especially mathematics is still low, with a KKM value of 6.5. Problems faced by MTs. Miftahul Ulum Ngembal and PGRI Tutur Islamic Middle School are: a) Lack of learning media that attracts students' attention. b) Lack of student learning motivation in learning mathematics, especially Linear Equation of One Variable. c) Student learning outcomes are low, namely with KKM 6.5. d) Lack of student understanding of algebra material, especially the system of linear equations of one variable. This is because this material is material that has just been received at the junior high school level. The solution offered is to provide Mathematics Comic Training for students of PGRI Tutur Islamic Middle School and MTs Mifathul Ulum Ngembal. This training aims to increase student learning motivation which will have an impact on student learning outcomes. This training will be held in 2 meetings so as not to disturb the learning and teaching process. In practice, students will be divided into groups. Each group will be given a mathematical comic that contains material about one variable linear equations and questions related to one variable linear equations.